DEVELOPMENT AND OPTIMIZATION OF ULTRASOUND EXTRACTION OF CHAMOMILE FLOWERS CHAMOMILLAE RECUTITA FLORES - E. Y. Zagorulko; A. A. Teslev; M. G. Ozhigova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2018)
The article deals with the development of ultrasound extraction technology of chamomile flowers. The aim of this work is working out and optimization of ultrasound extraction technology of the sum of flavonoids from chamomile flowers with further determination of the essential oil content in the extraction obtained. Materials and methods. The object of the research is the medicinal plant raw material (MRPM) of chamomile flowers (Chamomillae recutita ores) bought in a pharmacy. The extraction method is a two-level maceration with ultrasound procession of (MRPM). The extraction was performed in the ultrasound bath "Sapphire" of Technical and Commercial Center (TCC) (RMD) of 9.5 l. For the technological process optimal parameters determination of the sum of flavonoid extraction, the orthogonal factorial plan of Type 32 was built. Results and discussion. The following factors' influence on the extraction process of the sum of chamomile flowers flavonoids have been studied: the size of particles of (MRPM), the quantity of extraction steps, ethanol content in alcohol-water mixture, ratio (MRPM) /extragent, extraction time, media temperature. The regression equations describing the process of ultrasound extraction of chamomile flowers flavonoids at the first and second steps of maceration have been obtained. The following parameters of the technological process of chamomile flowers sum of flavonoids ultrasound extraction have been worked out: for the first step the extraction time was 22 min., the content of ethanol in alcoholwater mixture was 52% at the ratio MRPM/extragent 1:7 and the room temperature; for the second step: the extraction time was 27 min., the media temperature was 61°C at the ratio MRPM/extragent 1:5 (52% ethanol was used as an extragent). The general yield of the flavonoids sum was 97% and that of the essential oil was 81%. Thus, the ultrasound extraction technology of the sum of chamomile flowers flavonoids has been developed and optimized, allowing to obtain extracts with a high yield of the essential oil.